PERTANGGUNGJAWABAN PIDANA KORPORASI DALAM TINDAK PIDANA PENCUCIAN UANG DIKAITKAN DENGAN UNDANG-UNDANG NOMOR 8 TAHUN 2010 TENTANG PENCEGAHAN DAN PEMBERANTASAN TINDAK PIDANA PENCUCIAN UANG - Galumbang Hutapea (Program Studi Magister Ilmu Hukum Pascasarjana Universitas Langlangbuana, 2020)
ABSTRACT The remaining First Travel assets should be the rights of First Travel pilgrims who were deceived from the bully Umrah promo. In this case, the state did not suffer losses so the decision was considered wrong track. It should indeed be the rights of consumers, the next thing to know (assets) for the country. The research method used is descriptive analytical approach and normative juridical research specifications. While the data analysis uses qualitative juridical methods. Regulations concerning criminal liability for coporation in money laundering in Law No. 8 of 2010 there are still weaknesses. Efforts in preventing or overcoming money laundering by corporations are criminal law policies as a repressive approach in the form of criminalization of money laundering. Keywords: Criminal Liability, Corporations, Money Laundering